1996
DOI: 10.1111/j.1651-2227.1996.tb18225.x
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome: coagulation and clinical aspects

Abstract: The study aims were to review the clinical features of a group of patients with Noonan syndrome and to further elucidate their bleeding tendency. Eighteen patients (12M, 6F) aged 2.6–13.3 years underwent a clinical assessment, a questionnaire of their bleeding tendency and laboratory coagulation studies. Nine had cyanotic spells or breathing difficulties after birth; 11 had poor feeding or weight gain. Increased bruising or bleeding was reported in 12 (67%), four of whom had bleeding from the oral cavity. Exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The most common abnormalities include von Willebrand disease, deficiencies of factors XI and XII, and thrombocytopenia [Sharland et al, 1992b;Massarano et al, 1996;Singer et al, 1997]. Since many affected children will require interventional procedures such as balloon pulmonary valvuloplasty and orchidopexy, this is important to bear in mind to prevent significant hemorrhagic complications.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The most common abnormalities include von Willebrand disease, deficiencies of factors XI and XII, and thrombocytopenia [Sharland et al, 1992b;Massarano et al, 1996;Singer et al, 1997]. Since many affected children will require interventional procedures such as balloon pulmonary valvuloplasty and orchidopexy, this is important to bear in mind to prevent significant hemorrhagic complications.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Later studies showed a high frequency (56-67%) of coagulation defects in this patient group [Sharland et al, 1992;Massarano et al, 1996;Singer et al, 1997]. Sharland et al [1992] did detailed coagulation studies on 72 individuals with NS.…”
Section: Discussionmentioning
confidence: 96%
“…The same study reported combined FXI and FXII deficiency in one patient, combined FXI and FVIII deficiency in another patient, and combined FVIII, FXI, and FXII deficiencies in a third patient. Massarano et al [1996] investigated 18 patients with NS and found increased bruising or bleeding in 12 (67%). They detected prolonged aPTT in 10 cases (56%) linked with low activity levels of clotting factors, particularly FXI and FXII.…”
Section: Discussionmentioning
confidence: 97%
“…Easy bruising and bleeding problems have been reported in up to 55% of patients. Coagulation studies reveal prolonged bleeding time, factor VIII, XI and XII deficiencies, thrombocytopenia and platelet function defects [8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Noonan Syndrome (NS) is an autosomal dominant disorder characterized by short stature, typical facial dysmorphisms, congenital heart defects and other anomalies [8][9][10] such as bleeding problems which have been reported in up to 55% of patients [8][9][10][11][12][13][14]. NS is a clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%